The relationship between economic development and business ownership revisited - Carree, Martin; van Stel, André; Thurik, A. Roy; Wennekers, Sander (Cranfield University School of Management, 2007)
This paper revisits the two-equation model of Carree, van Stel, Thurik and Wennekers (2002) where deviations from the ‘equilibrium’ rate of business ownership play a central role determining both the growth of business ownership and that of economic development. Two extensions of the original setup are addressed: using longer time series of averaged data of 23 OECD countries (up to 2004) we can discriminate between different functional forms of the ‘equilibrium’ rate and we allow for different penalties for being above or under the ‘equilibrium’ rate. The additional data do not provide evidence of a superior statistical fit of a U-shaped ‘equilibrium’ relationship when compared to an L-shaped one. There appears to be a growth penalty for having too few business owners but not so for having too many.
Keywords: Entrepreneurship; Economic development; Economic growth; Business ownership